Optimization of Biofuel Production from Used Cooking Oil Using Natural Zeolite Catalyst - Isalmi Aziz; Siti Nurbayti; Reza Falepi (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2022)
Petroleum is still the primary energy used in the world. Its diminishing production is the trigger to find alternative energy to replace it. Biofuel is an alternative energy that has the potential to replace petroleum because it is renewable, environmentally friendly, and easy raw material. Waste such as used cooking oil can be used as raw material for making biofuels. The low price can reduce the cost of biofuel production. The conversion of oil into biofuel can be done using catalytic cracking with natural zeolite as a catalyst. This study aims to determine the optimum conditions for making biofuel from used cooking oil and determine its physical and chemical properties. The catalytic cracking process is carried out using an autoclave reactor. Used cooking oil and natural zeolite were introduced into the reactor, and the reaction was carried out by varying the time (1, 2, 3 hours), temperature (325, 350, 375oC), catalyst concentration (3, 5, 7%), and catalyst size. The product is distilled to produce biofuel (liquid), gas, and residue. The optimization results show that 3 hours, a temperature of 375oC, a catalyst concentration of 7%, and a catalyst size of 180µm are the optimum conditions for catalytic cracking with 44.94% biofuel yield. The resulting biofuel contains 73.48% hydrocarbons and 26.52% fatty acids. The hydrocarbon composition consists of 19.32% gasoline, 12.82% kerosene, and 35.11% diesel. The density of the biofuel produced is 0.8835g/mL, the flashpoint is 68oC, and the pourpoint is 27oC.